MENINGKATKAN KEMAMPUAN DAN KETERAMPILAN SISWA DALAM MEMBACA PUISI MELALUI METODE DEMONSTRASI - -, Susilowati (PEDAGOGIA, 2016)
This study aimed fatherly improve the quality of guidance and counseling program at the high school level with a focus issue focused on improving Tutoring Service Orientation Learning can be overcome anxiety students choose majors in high school and what efforts can be done counselor in helping students for placement and majors.The study design is described in a spiral of action research based on the adaptation of Hopkins with two cycles and each cycle of four phases of activity. Based on research data processing is found that the implementation of the guidance service learning orientation can overcome the anxiety level of students in the selection of majors in high school. This is evidenced by the level of student anxiety before any action guidance to the class X.3 in SMA Negeri 1 Bojongmangu amounted to 76.32%. After the action guidance of experienced reductions of students who experience anxiety. It was assest with the percentage decrease from the first cycle, up to the second cycle of 34.21%. Activity in the study orientation guidance services provides guidance information in groups major classical and small discussion groups. The results of this study are useful to enhance the role of coaching and guidance counselor in helping students with guidance and program implementation counselingg in SMAN 1 Bekasi regency, in particular, Bojongmangu.